Platelet Rich Concentrate Promotes Early Cellular Proliferation and Multiple Lineage Differentiation of Human Mesenchymal Stromal Cells In Vitro. (10th November 2014) - Shani, Samuel; Ahmad, Raja Elina; Vasudevaraj Naveen, Sangeetha; Murali, Malliga Raman; Puvanan, Karunanithi; Abbas, Azlina Amir; Kamarul, Tunku
Abstract : Platelet rich concentrate (PRC) is a natural adjuvant that aids in human mesenchymal stromal cell (hMSC) proliferation in vitro ; however, its role requires further exploration. This study was conducted to determine the optimal concentration of PRC required for achieving the maximal proliferation, and the need for activating the platelets to achieve this effect, and if PRC could independently induce early differentiation of hMSC. The gene expression of markers for osteocytes (ALP, RUNX2), chondrocytes (SOX9, COL2A1), and adipocytes (PPAR- γ ) was determined at each time point in hMSC treated with 15% activated and nonactivated PRC since maximal proliferative effect was achieved at this concentration. The isolated PRC had approximately fourfold higher platelet count than whole blood. There was no significant difference in hMSC proliferation between the activated and nonactivated PRC. Only RUNX2 and SOX9 genes were upregulated throughout the 8 days. However, protein expression study showed formation of oil globules from day 4, significant increase in ALP at days 6 and 8 ( P ≤ 0.05 ), and increased glycosaminoglycan levels at all time points ( P < 0.05 ), suggesting the early differentiation of hMSC into osteogenic and adipogenic lineages. This study demonstrates that the use of PRC increased hMSC proliferation and induced early differentiation of hMSC into multiple mesenchymal lineages, without preactivation or addition of differentiation medium.